Dose, exposure, and treatment regimen of intravenous immunoglobulin G in multifocal motor neuropathy - Li, Zhaoyang; Roepcke, Stefan; Franke, Ryan; Yel, Leman (Frontiers in Neurology, 2024)
IntroductionIntravenous immunoglobulin (IVIG) is the only approved treatment for multifocal motor neuropathy (MMN), a rare, chronic, immune-mediated demyelinating neuropathy. There is a significant gap in understanding of the role of serum immunoglobulin G (IgG) levels in the efficacy of IVIG in affected patients. We aimed to characterize the interplay between dose and exposure of IVIG and the effects of patient factors on individual variabilities.MethodsSerum IgG trough concentration data from a phase 3, randomized, double-blind, placebo-controlled, crossover trial of IVIG 10% in 44 patients with MMN (NCT00666263) were analyzed using fit-for-purpose population PK modeling. Patient factors were tested as covariates, and IgG PK profiles following various dosing regimens were simulated.ResultsSerum IgG levels, with significant inter-patient variability, correlated with dose and treatment interruptions at the individual patient level. Simulated data for various dosing regimens (0.4–2 g/kg once every 1–4 weeks [Q1–4W]) revealed that more frequent dosing provided more stable IgG levels than less frequent dosing, and dose splitting over multiple days had no significant effects on PK.DiscussionIn patients with MMN, stable dosing and consistent serum IgG levels are crucial to avoid negative responses owing to treatment interruptions. Dosing intervals more frequent than Q4W may alleviate periodic symptom deterioration. Dose splitting potentially offers flexibility for patients requiring large volumes of IVIG without negatively affecting serum IgG PK, while maintaining treatment efficacy. Variability in serum IgG levels between patients suggests that individualizing IVIG treatment regimens and target IgG levels may play a key role in managing MMN.